Peningkatan Kemampuan Membaca Al-Quran Pada Mata Pelajaran PAI dan Budi Pekerti Aspek Al-Qur’an Hadis untuk Siswa Kelas X TKJ 4 di SMKN 1 Badegan Ponorogo - Wahyu Triana, Anis (LP. Ma'arif Janggan Magetan, 2022)
This study aims to determine whether there is an increase in the ability to read the Koran in class X TKJ 4 at SMKN 1 Badegan Ponorogo after using the reading-aloud method. This research is classroom action research, and the data collection technique in this study is by observation and student ability tests. The results showed that: (1) the teacher's activity qualifications in cycle I was categorized as